Private provision of public goods that are complements for private goods: Application to open source software developments - Noriaki Matsushima; Ryusuke Shinohara (Osaka University, Institute of Social and Economic Research (ISER), 2012)
This paper examines the questions of who participates in the provision of a public good through the voluntary participation of agents in the presence of strong complementarity between a public good and a private good. We show that the greater the initial endowment of the private good that agents have, the more likely they are to participate in the provision of the public good. Whether an agent participates does not depend on the efficiency of his/her technology for production of the public good. We extend the basic model and introduce a simple transfer game. We show a sufficient condition so that the voluntary transfer scheme achieves Pareto efficiency.
Keywords: C72; H41; L17; 330; public goods; voluntary participation; strong complementarity; transfer of private goods; Öffentliche Güter; Open Source; Komplementärgut; Nichtkooperatives Spiel; Agentenbasierte Modellierung; Theorie